2015
DOI: 10.1371/journal.pone.0123398
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Subarachnoid Hemorrhage in Rats: Comparison of Two Endovascular Perforation Techniques with Respect to Success Rate, Confounding Pathologies and Early Hippocampal Tissue Lesion Pattern

Abstract: Recently aside from the “classic” endovascular monofilament perforation technique to induce experimental subarachnoid hemorrhage (SAH) a modification using a tungsten wire advanced through a guide tube has been described. We aim to assess both techniques for their success rate (induction of SAH without confounding pathologies) as primary endpoint. Further, the early tissue lesion pattern as evidence for early brain injury will be analyzed as secondary endpoint. Sprague Dawley rats (n=39) were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
10
2
Order By: Relevance
“…Interestingly we found higher expression levels of both cytokines in the hippocampus compared to parietal and basal cortical regions in sham animals with a tendency towards even lower expression after SAH. As recently shown by our groups [21, 28], selective neuronal death in hippocampal subareas can be detected very early after SAH, which may at least in part explain the tendency of lower expression levels in SAH animals. However, the unexpected cytokine expression levels in the hippocampus remains unclear and needs further investigation.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly we found higher expression levels of both cytokines in the hippocampus compared to parietal and basal cortical regions in sham animals with a tendency towards even lower expression after SAH. As recently shown by our groups [21, 28], selective neuronal death in hippocampal subareas can be detected very early after SAH, which may at least in part explain the tendency of lower expression levels in SAH animals. However, the unexpected cytokine expression levels in the hippocampus remains unclear and needs further investigation.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally activation of caspase 3 was assessed by immunohistochemistry using a rabbit monoclonal antibody against cleaved caspase 3 (Rabbit anti-cleaved Caspase-3 (Asp175), monoclonal, Cat # 9664, Cell Signaling Technology, Danvers, MA, USA) according to the protocol recommended by the manufacturer. Brain slices from an animal 6 hours after induction of subarachnoid hemorrhage served as positive control for the staining [ 24 ]. Animals not surviving until day 7 were excluded from histopathological analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite numerous basic discoveries in SAH animal research, few have turned out to be effective in clinical trials on humans. Moreover, oftentimes, animal research findings do not translate into human medicine due to incomplete replication of human pathophysiology [40][41][42] . Here, we have demonstrated that TRAF3 expression was elevated after clinical SAH and was mainly expressed in neurons, suggesting that downregulation of TRAF3 may have potential clinical application in the treatment of EBI.…”
Section: Discussionmentioning
confidence: 99%